The Relationship between Response Inhibition and Cognitive Flexibility with Behavioral Symptoms in Children with High Functioning Autism - Vali Shiri; Ali Hoseyni; Ebrahim Pishyareh; Vahid Nejati; Akbar Biglareyan (Vesnu Publications, 2015)
Introduction: The association of autism symptoms and cognitive abilities can facilitate the etiology and treatment of autism disorders. Destruction of executive functions seems to be one of the cognitive reasons of potential phenotype in autistic disorder. Thus, the present paper aims to study the relationship between response inhibition and cognitive flexibility with autistic symptoms. Materials and Methods: In this cross-sectional study, 50 children with high-Functioning autism were selected using convenience sampling method with the High-Functioning Autism Spectrum Screening Questionnaire (ASSQ). Then the Gilliam Autism Rating Scale (GARS) was completed by therapist and neuropsychological tests of stroop and cognitive flexibility scale were taken by the subjects. Pearson correlation coefficient and multi-variant regression were used for data analysis. Results: There is a significant negative relationship between response inhibition with communicative and social interaction symptoms (P < 0.01, P < 0.05, P < 0.001). There is a significant negative relationship between cognitive flexibility with communicative, social interaction and stereotype behavior symptoms (P < 0.01, P < 0.05). The results of regression analysis also show that response inhibition can predict communication symptoms. Cognitive flexibility can predict social interaction symptoms (P < 0.01, P < 0.05). Conclusion: The results obtained by this study indicate the significant role of response inhibition and cognitive flexibility in autistic symptoms. Thus, it is recommended to consider executive functions for new treatment of children with autism disorder.